2003
DOI: 10.1029/2003gl017193
|View full text |Cite
|
Sign up to set email alerts
|

Strong ground motion and damage in the Taipei basin from the Moho reflected seismic waves during the March 31, 2002, Hualien, Taiwan earthquake

Abstract: The March 31, 2002, Hualien offshore earthquake (ML6.8, Mw7.0) caused minor damage near its epicenter but significant damage in Taipei, about 110 km from the epicenter. The recorded PGA values around the Taipei basin vary in a factor of 5. The high‐PGA values in the southeastern part of the basin correspond to the most significant damage area during the earthquake. Strong ground‐motion recordings from this event recorded at stations around the Taipei basin exhibit several distinct large‐amplitude seismic arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…The area has ex pe ri enced sev eral dam ag ing earth quakes, the most re cent of which oc curred on 31 March 2002. The re sults of pre vi ous re search on earth quake ground mo tion pe cu liar i ties in the Tai pei ba sin (e.g., Kuo et al 1995;Wen et al 1995;Loh et al 1998;Wen and Peng 1998a, b;Sokolov and Jean 2002;Wang and Lee 2002;Chen 2003;Fletcher and Wen 2005) showed that large lat eral vari a tions in ground-mo tion char ac ter is tics (peak ground ac cel er ation, re sponse spec tra, dom i nant fre quen cies, etc.) are appar ent.…”
Section: Introductionmentioning
confidence: 99%
“…The area has ex pe ri enced sev eral dam ag ing earth quakes, the most re cent of which oc curred on 31 March 2002. The re sults of pre vi ous re search on earth quake ground mo tion pe cu liar i ties in the Tai pei ba sin (e.g., Kuo et al 1995;Wen et al 1995;Loh et al 1998;Wen and Peng 1998a, b;Sokolov and Jean 2002;Wang and Lee 2002;Chen 2003;Fletcher and Wen 2005) showed that large lat eral vari a tions in ground-mo tion char ac ter is tics (peak ground ac cel er ation, re sponse spec tra, dom i nant fre quen cies, etc.) are appar ent.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (Wen et al 1995a(Wen et al , b, 1999Wen and Peng 1998;Sokolov et al 2000bSokolov et al , 2001Sokolov and Jean 2002;Chen 2003;Fletcher and Wen 2005) did such studies in the TMA. Wen and Peng (1998) and showed that the spatial distribution of site amplifications depends on the incidence direction of waves into the Taipei Basin.…”
Section: Strong Ground Motionsmentioning
confidence: 99%
“…A major cause of building vibration is earthquake-induced ground motions. Chen (2003) reported that a distant earthquake (M w 7.0) in 2002 caused two massive construction cranes on TAIPEI 101 to fall from the 56 th floor to the ground. Other factors include: strong winds, volcanic eruptions, explosions, and landslides.…”
Section: Introductionmentioning
confidence: 99%